BATUAN LOKAL PACITAN (DRUZY) DALAM PENCIPTAAN PERHIASAN PERAK INOVATIF - Alvi Luviani (Corak : Jurnal Seni Kriya, 2014)
The creation of innovative jewelry using local gem stone Pacitan (Druzy) isconsidered to be essential in addition to introduce Indonesia's natural wealth in the form ofjewelry and also shows that the local gem stone can look elegant, high qualified and tasteglobally if we can mix and match it with other appropriate supporting material and innovativedesign .The method used in the creation of innovative jewelry using this Druzy stone is amethod of exploration, experimentation and the materialization according to the stage in thecreation of craft art.Contribution that can be given in the creation of silver jewelry by utilizing local gemstone are able to increase the awareness of Indonesia people that a lot of potential naturalwealth around us that still unprocessed wisely and creatively. If the ability to process thenatural wealth is more refined, it will create a lot of local jewelry products that has world-classquality. In addition, those innovative jewelry products would enrich the world of art jewelry inIndonesia and speaks at the international level bringing the identity and culture of the nation. Key words: Silver jewelry, innovative, Druzy local gemstone  Penciptaan perhiasan inovatif dengan menggunakan batuan local Pacitan (druzy ) inidirasa penting selain untuk lebih memperkenalkan kekayaan alam Indonesia dalam bentukperhiasan juga untuk menunjukan bahwa batuan local dapat tampil elegan, berkelas danbercita rasa global apabila kita dapat memadu padankannya dengan material pendukung lainyang tepat dengan desain yang inovatif.Metode yang digunakan dalam penciptaan perhiasan inovatif dengan menggunakanbatu druzy ini adalah metode eksplorasi, eksperimen dan perwujudan sesuai dengan tahappenciptaan dalam seni kriya.Kontribusi yang dapat diberikan dalam penciptaan perhiasan perak denganmemanfaatkan batuan local ini adalah dapat semakin meningkatkan kesadaran masyarakatluas Indonesia bahwa banyak sekali potensi alam yang ada di sekitar kita yang belum diolahsecara bijak dan kreatif. Apabila kemampuan mengolah tersebut semakin terasah, maka akan banyak sekali tercipta produk perhiasan bermuatan local dengan cita rasa global. Selain itukarya perhiasan inovatif ini mampu memperkaya khasanah dunia seni perhiasan di Indonesiasekaligus berbicara di kancah internasional tanpa meninggalkan jati diri dan budaya bangsa.Kata kunci: Perhiasan perak, inovatif, batuan local Druzy